AB0111 Prognostic significance of limited and difusse form of skin changes in systemic sclerosis. (1st June 2001) - Damjanov, N; Dobrosavljevic, G; Pavlov, S; Radunovic, G; Djurdjic, I; Todorvic, N; Milenkovic, M; Ostojic, P
Abstract : Background: Objectives: To assess the difference in frequency of pulmonary and renal involvement, as well as lungs insufficiency and renal failure between patients (pts) with limited cutaneous Systemic Sclerosis (lcSSc) and difusse cutaneous Systemic Sclerosis (dcSSc). Methods: Group of 138 pts with Systemic Sclerosis (SSc), 127 females and 11 males, age 28–75 years (median 53), were followed for 3–26 (median 13) years period. Extent of skin involvement was recorded, and pts were examined for radiographic signs of pulmonary fibrosis, carbon monoxide transfer (TCO) factor (done in 28 pts), and renal involvement and failure (urine sediment, creatinin clearance, arterial tension). Difference of visceral involvement, pulmonary insufficiency and renal failure between pts with lcSSc and dcSSc was correlated. Results: Among 138 pts, 105(76%) had lcSSc, and 33(24%) dcSSc. Pulmonary lession were found in 40/105 pts with lcSSc, and in 25/33 pts with dcSSc (p = 0, 004-χ 2 test). Renal lession was detected in 11/105 pts with lcSSc, and in 8/33 pts with dcSSc (p = 0, 04-χ 2 test). Signs of lung insufficiency developed in 30/105 pts with lcSSc, and in 18/33 pts with dcSSc (p = 0, 04-χ 2 test). Lower creatinin clearance and high arterial blood preasure were detected in all patients with recorded renal lession during the follow up period (in 11/105 pts with lcSSc, and in 8/33 pts with dcSSc). Renal failure was significantly more frequent in dcSSc pts (p = 0, 04-χ 2 test). In 7(21%) pts with dcSSc no criteria for pulmonary and renal involvement were present during the follow up period. On the other hand, in 14(13%) pts with lcSSc pulmonary insufficiency or renal. Conclusion: Difusse cutaneous lessions were prognostic sign of lungs and kidneys involvement, as well as pulmonary insufficiency and renal failure in most of the patients, but about 20% of the dcSSc patients were without severe visceral lessions during the 13 years of follow up period. On the other hand, 13% of patients with limited cutaneous lessions had bad prognosis and developed pulmonary insufficiency or renal failure in first 5 years of disease duration.